FACTORS RELATED TO HYPERTENSION CONTROL IN THE ELDERLY AT PUSKESMAS BANTEN GIRANG YEAR 2024 - Nita Nofita; Ismarina; Lukman Waris (ZILLZELL MEDIA PRIMA, 2024)
Hypertension is still the most common health problem experienced by the world's population. Hypertension is a condition of a person who has systolic blood pressure ≥140 mmHg and diastolic pressure ≥90 mmHg. The high prevalence of hypertension in the elderly group is caused because with age, resulting in a decrease in physiological functions of the body, so that non-communicable diseases begin to appear. Hypertension control behavior is the main thing to prevent complications, such as stroke, coronary heart disease, and kidney failure. This study aims to determine the factors associated with elderly behavior in controlling hypertension. This type of research is quantitative with a cross sectional design. Independent variables are gender, education level, lifestyle. While the dependent variable is the control behavior of hypertension in the elderly. The population of all hypertensive patients recorded in the Banten Girang Health Center work area in 2023. The sample number of 100 people was selected by purposive random sampling. Statistical test using Chi square test with 95% CI and logistic regression test. The results of statistical tests showed that sex and education variables did not have a significant relationship with hypertension control behavior in the elderly (p > 0.05), while lifestyle variables with p = 0.003 OR = 4,902, and family support variables with p = 0.010 OR = 3,778 which means they have a meaningful relationship with hypertension control behavior in the elderly.